2015
DOI: 10.1124/dmd.115.063925
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Evaluation for Substrate Selectivity of Cynomolgus Monkey Cytochrome P450 2C9, a New Efavirenz Oxidase

Abstract: Cynomolgus monkeys are widely used as primate models in preclinical studies, because of their evolutionary closeness to humans. In humans, the cytochrome P450 (P450) 2C enzymes are important drug-metabolizing enzymes and highly expressed in livers. The CYP2C enzymes, including CYP2C9, are also expressed abundantly in cynomolgus monkey liver and metabolize some endogenous and exogenous substances like testosterone, S-mephenytoin, and diclofenac. However, comprehensive evaluation regarding substrate specificity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 19 publications
(30 reference statements)
1
17
0
Order By: Relevance
“…Interspecies differences regarding caffeine oxidation exist, but the predominant C-8-hydroxylation of caffeine in rodents and rabbits have been shown to be broadly similar [31]. Although efavirenz is known as a probe substrate for human P450 2B6, efavirenz was oxidized in a limited manner by cynomolgus monkey P450 2B6 but efficiently by cynomolgus monkey P450 2C9 [13] (Table 3). Liquid chromatography-mass spectrometry analysis revealed that both cynomolgus monkey P450 2C9 and human P450 2B6 formed the same 8-hydroxy-and 8,14-dihydroxy-efavirenz [13].…”
Section: Limited Different Roles Of P450 Enzymes In Drug Oxidations Imentioning
confidence: 94%
See 3 more Smart Citations
“…Interspecies differences regarding caffeine oxidation exist, but the predominant C-8-hydroxylation of caffeine in rodents and rabbits have been shown to be broadly similar [31]. Although efavirenz is known as a probe substrate for human P450 2B6, efavirenz was oxidized in a limited manner by cynomolgus monkey P450 2B6 but efficiently by cynomolgus monkey P450 2C9 [13] (Table 3). Liquid chromatography-mass spectrometry analysis revealed that both cynomolgus monkey P450 2C9 and human P450 2B6 formed the same 8-hydroxy-and 8,14-dihydroxy-efavirenz [13].…”
Section: Limited Different Roles Of P450 Enzymes In Drug Oxidations Imentioning
confidence: 94%
“…Although efavirenz is known as a probe substrate for human P450 2B6, efavirenz was oxidized in a limited manner by cynomolgus monkey P450 2B6 but efficiently by cynomolgus monkey P450 2C9 [13] (Table 3). Liquid chromatography-mass spectrometry analysis revealed that both cynomolgus monkey P450 2C9 and human P450 2B6 formed the same 8-hydroxy-and 8,14-dihydroxy-efavirenz [13]. An anti-histaminic drug ebastine has been recognized as a human P450 2J2 probe, but also partly Table 3 Typical substrates for marmoset, cynomolgus monkey, and human P450 enzymes.…”
Section: Limited Different Roles Of P450 Enzymes In Drug Oxidations Imentioning
confidence: 98%
See 2 more Smart Citations
“…Marmoset P450 2C8, 2C18, 2C19, 2C58, and 2C76 also catalyzes 7-pentoxyresorufin O-deethylation. Similarly, cynomolgus monkey P450 2C9 and 2C19 metabolize many human P450 2C substrates, but also show some limited differences in drug oxidations of human P450 2C substrates (Hosaka et al, 2015b). Interestingly, marmoset P450 2C58 had the highest catalytic activities among five marmoset P450s tested toward non-P450 2C substrates, such as ethoxyresorufin, 7-ethoxycoumarin, coumarin, 7-pentoxyresorufin, and chlorzoxazone, whereas cynomolgus monkey P450 2C58 and human P450 2C58 were both pseudogenes.…”
Section: Discussionmentioning
confidence: 99%